UTILIZATION OF WHOLE EXOME SEQUENCING DATA TO IDENTIFY CLINICALLY RELEVANT PHARMACOGENOMIC VARIANTS IN INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Mulder, Daniel; Khalouei, Sam; Warner, Neil; Gonzaga-Jauregui, Claudia; Church, Peter; Walters, Tom; Ramani, Arun; Griffiths, Anne; Cohn, Iris; Muise, Aleixo
Abstract: Objectives: We hypothesized that variants within clinically relevant pharmacogenes could be identified using a whole exome sequencing (WES) dataset derived from a cohort of over 1000 IBD patients. Methods: Pediatric patients diagnosed with IBD underwent WES. We selected 18 genes with supporting literature where specific exonic variants would influence clinical care. Results: We identified actionable pharmacogenes variants in 63% of patients. Importantly, 5% of IBD patients were at risk for serious adverse effects from anaesthesia and 3% were at increased risk for thrombosis. Conclusions: We identified exonic variants in the majority of our IBD patients that directly impact clinical care. Flowchart of our pharmacogenomic analysis pipeline. After enrolment (n=2309), each patient underwent whole exome sequencing and sequence alignment. Available family members were also sequenced. Analyzed samples were limited to patients and family members with IBD (n=1097). Pharmacogenes relevant to patients with IBD were identified by literature review and evaluation of pharmGKB (total of 18 genes). Variant filtering was performed using Stargazer and GEMINI frameworks. In our cohort, there were 8 relevant pharmacogenes with variants that would alter clinical care based on current guidelines and standard of care. 63% of the patients had at least one variant that could impact care.